Drivers of Foliar Fungal Endophytic Communities of Kudzu (Pueraria montana var. lobata) in the Southeast United States - Maryam Shahrtash; Shawn P. Brown (Diversity, 2020)
Fungal endophytes play important roles in plant fitness and plant–microbe interactions. Kudzu (Pueraria montana var. lobata) is a dominant, abundant, and highly aggressive invasive plant in the Southeast United States. Kudzu serves as a pathogen reservoir that impacts economically important leguminous crops. We conducted the first investigations on kudzu fungal endophytes (Illumina MiSeq—ITS2) to elucidate drivers of endophytic communities across the heart of the invasive range in the Southeast United States (TN, MS, AL, GA). We tested the impacts of multiple environmental parameters (Chlorophyll, NO3−, K+, soil pH, leaf area, host genotype, traffic intensity, and geographic location) on foliar endophyte communities. Endophytic communities were diverse and structured by many factors in our PerMANOVA analyses, but location, genotype, and traffic (proxy for pollution) were the strongest drivers of community composition (R2 = 0.152, p < 0.001, R2 = 0.129, p < 0.001, and R2 = 0.126, p < 0.001, respectively). Further, we examined the putative ecological interactions between endophytic fungi and plant pathogens. We identify numerous OTUs that are positively and strongly associated with pathogen occurrence, largely within the families Montagnulaceae and Tremellales incertae sedis. Taken together, these data suggest location, host genetics and local pollution play instrumental roles in structuring communities, and integrative plant management must consider these factors when developing management strategies.